2022
DOI: 10.1017/s0033291722002732
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to psychotropic medications and mortality in schizophrenia: a 5-year national cohort study

Abstract: Background Relatively few studies have explored the differential contributions of the accumulative dosage of psychotropic medications on mortality in patients with schizophrenia. Methods We aimed to explore the effects of the exposure dosage of psychotropic medications on mortality during a follow-up period of 5 years with a national cohort of individuals with schizophrenia in 2010. Causes of death were linked through Taiwan's National Mortality Registry. The mean defined daily dose of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Similar findings considering antidepressant use have been found in a previous study comparing different levels of antidepressant exposure with non-use (15–40% lower risk depending on the level of exposure) 9 . Another study comparing the levels of antidepressant exposure found 17% lower risk associated with low exposure and 9% lower risk with moderate exposure, but there was no difference in risk with the highest exposure 10 . Similar trend was also seen in a previous Finnish study, even though the results were not statistically significant (HR 0.57, 95% CI, 0.28–1.16) 13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar findings considering antidepressant use have been found in a previous study comparing different levels of antidepressant exposure with non-use (15–40% lower risk depending on the level of exposure) 9 . Another study comparing the levels of antidepressant exposure found 17% lower risk associated with low exposure and 9% lower risk with moderate exposure, but there was no difference in risk with the highest exposure 10 . Similar trend was also seen in a previous Finnish study, even though the results were not statistically significant (HR 0.57, 95% CI, 0.28–1.16) 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have assessed the effectiveness of antidepressant use in persons with schizophrenia in real-world settings. A previous U.S. study evaluated several outcomes related to the effectiveness and safety aspects of antidepressant augmentation 12 , and two previous studies have assessed the association between antidepressant use and mortality in schizophrenia in Nordic countries 9 , 13 , and one study in Taiwan 10 . To our knowledge, there are no previous studies investigating the effectiveness of specific antidepressants in real-world settings.…”
Section: Introductionmentioning
confidence: 99%
“…People living with schizophrenia are commonly reliant on a combination of pharmaceuticals such as antipsychotics, antidepressants, anxiolytics, and antimanic medications. 56 A number of these medications, such as clozapine and olanzapine, cause significant metabolic dysfunction, thought to impair cognitive function. 57 The impact of other medications used in schizophrenia on cognition is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the 20-year follow-up of the nationwide cohort of 62,250 patients with schizophrenia in Finland confirmed that long-term antipsychotic use does not increase severe physical morbidity in patients with schizophrenia, but rather is associated with substantially decreased mortality, especially among patients treated with clozapine [ 82 ]. Most recently, a large 5-year national cohort study in Taiwan that involved 102,964 patients with schizophrenia found that antipsychotic exposure of patients had been associated with better survival outcomes in all-cause mortality, particularly when adequate dosages were used [ 83 ]. It is worthy to mention that the use of second-generation long-acting injectable antipsychotics (LAIs) has been associated with the lowest mortality risk in patients with schizophrenia [ 84 ], whereas LAIs decreased all-cause mortality and suicide risk in newly diagnosed patients with schizophrenia [ 85 ].…”
Section: Protective Factorsmentioning
confidence: 99%